Innovative Behavior And Performance Of Local Government Employees - Sinaga, Anggun Tiur Ida; Sibagariang, Susy Alestriani (LPPM Universitas PGRI Sumatera Barat, 2025)
Improving employee performance in public organizations, such as local governments, faces increasingly complex challenges, especially with the rapid development of digital technology. The purpose of this study is to analyze how innovative behavior can improve the performance of local government employees. Data collection for analysis was conducted using a questionnaire as the primary data collection tool. The study sample size was 786 people. Data analysis used descriptive statistics and Structural Equation Modeling (SEM)-PLS. The results of the study showed that the coefficient of determination (r-square) value of the performance variable was 0.454, which means that innovative work behavior was able to influence performance by 45.4%. Furthermore, the results indicate that innovative behavior has a positive and significant effect on the performance of local government employees in North Sumatra province. The novelty in conducting this research is to increase curiosity for improvement and the ability to discover new techniques/equipment, the government must provide opportunities for employees to pour ideas and thoughts into the work process.